2014
DOI: 10.1037/a0036912
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of motivational interviewing for adolescent health behavior: Efficacy beyond substance use.

Abstract: MI interventions for adolescent health behavior appear to be effective. In addition, the magnitude of the aggregate effect size does not appear to differ meaningfully from reports of interventions targeting only substance use in adolescents. However, significant lack of clarity exists regarding interventionist training requirements necessary to ensure intervention effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 38 publications
2
77
2
2
Order By: Relevance
“…These conclusions were surprising, as they are discrepant with conclusions of other reviews on similar interventions with similar effect sizes 1, 14, 15. This review's conclusions indicate that the field should discuss what should be expected from brief interventions and how best to use them—or to caution their dissemination and focus more research on alternative intervention approaches, as suggested by a recent individual participant data (IPD) meta‐analysis of a subset of trials evaluating brief motivational interventions for college student drinking 16, 17.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…These conclusions were surprising, as they are discrepant with conclusions of other reviews on similar interventions with similar effect sizes 1, 14, 15. This review's conclusions indicate that the field should discuss what should be expected from brief interventions and how best to use them—or to caution their dissemination and focus more research on alternative intervention approaches, as suggested by a recent individual participant data (IPD) meta‐analysis of a subset of trials evaluating brief motivational interventions for college student drinking 16, 17.…”
Section: Introductionmentioning
confidence: 64%
“…Given the above, we were surprised by the review's strong conclusions unfavorable to MI, especially as the review authors noted that their conclusions differed from another Cochrane review on MI for drug use, even though the other review had similar effect sizes 41. Discrepancies in interpreting similar effect sizes for similar interventions indicate that MCIDs are not defined uniformly in this area, and the review authors’ conclusions represent a particular interpretation of effects (rather than the effects themselves) that differs from other review authors’ interpretations 1, 14, 15.…”
Section: Sustainability and Clinical Significance Of Intervention Effmentioning
confidence: 84%
See 1 more Smart Citation
“…Several practical strengths of motivational interviewing lend support for incorporating its principles into juvenile probation practice: the intervention can be administered in the limited time available for meeting with probationers (Cushing, Jensen, Miller, & Leffingwell, 2014;Walters, Alexander, & Vader, 2008); the style of motivational interviewing is developmentally appropriate for adolescents (Feldstein & Ginsburg, 2006); and interventions based on motivational interviewing have While motivational interviewing was initially designed to treat substance use disorders among adults (Miller & Rollnick, 2012), its defining skills have been applied with a variety of populations to successfully address maladaptive behaviors and encourage positive behavior change. For example, when compared to an alternative or no treatment, motivational interviewing has generally been associated with improved adult and adolescent patient outcomes over a range of clinical healthcare settings and disorders, including successful management of diabetes, asthma, obesity, as well as problematic substance use (see Cushing et al, 2014;Gayes & Steele, 2014;Hettema, Steele, & Miller, 2005;Jensen et al, 2011;Lundahl, Kunz, Brownell, Tollefson, & Burke, 2010;Rubak, Sandbaek, Lauritzen, & Christensen, 2005, for review). Motivational interviewing has also been lauded within criminal justice settings for its demonstrated effectiveness in increasing rule compliance and reducing criminal recidivism among adult offenders (McMurran, 2009;Walters, Vader, Nguyen, Harris, & Eells, 2010).…”
Section: Motivational Interviewing Skillsmentioning
confidence: 99%
“…[64][65][66][67] MI is defined as a collaborative, person-centered approach to help support motivation for change and is a well-supported intervention strategy for increasing exercise in both adolescents and adults. [64][65][66][67] The goal of MI is to allow the AYA to become the primary advocate and agent for change through the exploration and resolution of ambivalence toward exercise. The four basic principles of MI include expressing empathy, developing discrepancy, rolling with resistance, and supporting self-efficacy.…”
Section: Motivational Interviewingmentioning
confidence: 99%